Eksplorasi Etnomatematika dalam Arsitektur Rumah Adat Suku Komering untuk Pembelajaran Geometri - Agustian, Linda; Sastrawati, Eka; Indryani (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to explore the ethnomathematical elements in the architecture of traditional Komering houses and examine their potential as contextual geometry learning resources in elementary schools. The research employed a qualitative method with an ethnographic approach, using direct observation, in-depth interviews, and visual documentation in Sukajadi Village, East Ogan Komering Ulu Regency, South Sumatra. The findings reveal that Komering traditional houses contain various geometric concepts such as triangles, rectangles, trapezoids, circles, and cuboids, implemented in the roof, walls, stairs, and decorative ornaments. The study concludes that integrating local culture through an ethnomathematical approach can enhance students' understanding of geometric concepts in a more concrete manner. The implication of this research suggests that Komering traditional houses are appropriate as innovative learning media that support the Merdeka Curriculum and preserve local cultural heritage.